1998
DOI: 10.1038/sj.ijo.0800641
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the effect of ethnic group on weight concern: finding a role for family values

Abstract: OBJECTIVE: To examine the impact of ethnic group on aspects of weight concern and to assess the role of family values in explaining this association. SUBJECTS AND MEASURES: 20 Asian and 20 white daughters gave a questionnaire to their mother, father and sibling closest in age, concerning their pro®le characteristics (age, education) values and beliefs and completed a matched questionnaire containing additional measures of aspects of their weight concern. RESULTS: The results showed no differences between the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
1
16
1
Order By: Relevance
“…This suggests that other factors are contributing to the differences observed throughout all ethnic groups. As noted earlier, possible reasons for these differences may be due to cultural variations between ethnic groups regarding views about PA, physical fitness, and body image (22,36). However, evidence to support this notion is limited and therefore is in need of further investigation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This suggests that other factors are contributing to the differences observed throughout all ethnic groups. As noted earlier, possible reasons for these differences may be due to cultural variations between ethnic groups regarding views about PA, physical fitness, and body image (22,36). However, evidence to support this notion is limited and therefore is in need of further investigation.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, variations in height, weight, and maturation within each ethnic group may confound MRW and BMI scores observed in this sample. Furthermore, it's been suggested that socioeconomic status, parent education, and cultural beliefs may play a significant role in physical activity behavior (15,18,22), which may in turn contribute to variations in levels of cardiovascular fitness and body composition. However, these variables were not measured in this study and therefore only loose assumptions can be made in regards to their influence on this sample.…”
Section: Discussionmentioning
confidence: 99%
“…Garfinkel and Garner (1982) suggest that there are very few, if any, properly controlled studies on family issues and eating disorders. Since this observation in 1982, several studies have been documented focusing on the family attributes, personalities, attitudes, and values that may influence the development of an eating disorder (Brouwers, 1990;Kencller et a]., 1995;LeGrange, Eisler, Dare, Pr Russel, 1992;Ogden & Chanana, 1998). The role of each parent can have a significant impact on the development of bodyimage, sense of adequacy and self esteem, life goals, and feminine identification (Attie Pr Brooks-Gunn, 1999;O'Neil & White, 1987).…”
mentioning
confidence: 98%
“…They found that although Samoans ideal body shape was slim and they attempted to lose weight, they did not have negative views on obesity. Other studies 25,26 also contended that cultural beliefs were very powerful constructs when explaining the weight concern in different countries. The Chinese body culture likely offers a very different perspective than other cultures and this might explain these regression analysis results.…”
Section: Discussionmentioning
confidence: 99%